Blindaid: Assisting The Visually Impaired In Object Detection And Tracking Using Slam (International Journal of Environmental Sciences, 2025)
When a blind person loses something or forgets where they put it, it can be difficult and time-consuming to locate it. To address this problem, we created blindAid, an application that recognizes the object the user is using and recalls its most recent location. If the user needs the object and can't remember where he put it, the application will assist him in finding it by utilizing voice commands. This study proposes a new Internet of Things-based solution that combines advanced object recognition with Simultaneous Localization and Mapping (SLAM) technology.. We have made an IOT-model which can communicate with the application we have created. Voice recognition is enabled in the application to record user requests through voice commands and provide a speech output in response. The program can also operate in the background, eliminating the requirement for constant openness. This makes life easier for blind people and enhances the user experience.